Standard and Method Independent Units for Heparin Anticoagulant Activities - Hemker, H C; Béguin, S (Thrombosis and Haemostasis, 1993)
It is discussed why the current USP unit of heparin anticoagulant activity necessarily will render inaccurately the anticoagulant activities of low molecular weight heparins. It is shown that the outcome is bound to vary with the method used for comparison of the sample and the standard and with the nature of the standard used. As an alternative we define a unit of heparin in terms of anti-factor Xa- and antithrombin-activity that is independent of the heparin standard and of the assay method, but that is based upon a quantitative description of the catalytic effect of heparin on AT III mediated thrombin- and factor Xa breakdown. Expression of the results of existing anti-factor Xa- and antithrombin tests in terms of these units will allow to express heparin levels in plasma in terms of concentrations of active anticoagulant material. This approach makes it possible to separate heparin pharmacodynamics from heparin pharmacokinetics. Introduction of this unit does not require adaptation of current laboratory practice but changes the way in which the results obtained are expressed.